The novelty of tradition according to L. Pareyson (ALPHA. Journal of Arts, Literature and Philosophy, 2024)
The concept of tradition has been deeply criticised from the French Enlightenment to the present day. Everything that refers to the past, the uses and concepts in the fields of philosophy, aesthetics, politics, and society have undergone great changes in pursuit of emancipation and a quest to be themselves in a new and original way, without depending on antecedent instances. However, from the thought of Luigi Pareyson (1918-1991), we discover the need for a revitalisation of the concept of tradition to be able to develop a revelatory thought about truth, being, and human experience. The Italian philosopher's itinerary starts from aesthetics and the analysis of the role of matter in it to go back to the conception of philosophy as hermeneutics as an interpretation of truth. Tradition will constitute a fundamental notion for aesthetics and hermeneutics and, therefore, for philosophy in general.
Keywords: Tradition; Aesthetics; Hermeneutics; truth; Pareyson